2021
DOI: 10.1002/adfm.202109929
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabright and Highly Polarity‐Sensitive NIR‐I/NIR‐II Fluorophores for the Tracking of Lipid Droplets and Staging of Fatty Liver Disease

Abstract: Visualizing the progression of fatty liver disease in vivo is of great significance in biomedical research of fatty liver, but hindered by the lack of suitable approaches with deep penetration, high specificity, and real-time observability for fatty liver imaging. Herein, two bright NIR-I/NIR-II fluorophores with D-π-A-π-D structures are designed and synthesized for fatty liver tracking in vivo. Such fluorophores show an ultrahigh quantum yield of 49.2% and 17.3% at the emission maximum of 930 and 975 nm, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 59 publications
1
50
0
Order By: Relevance
“…Moreover, the ex vivo ratiometric images revealed that the signal ratio F 710 / F 790 enhanced from 1.14 in the liver of healthy mice to 1.58 in the liver of NAFL mice (Figure S18). All the results indicate that the liver polarity of NAFL mice is lower than that of healthy mice, which was consistent with previous reports in the literature. , Cy-Mp can be used as a potential tool for diagnosing NAFL by tracking the polarity disorder of the liver.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the ex vivo ratiometric images revealed that the signal ratio F 710 / F 790 enhanced from 1.14 in the liver of healthy mice to 1.58 in the liver of NAFL mice (Figure S18). All the results indicate that the liver polarity of NAFL mice is lower than that of healthy mice, which was consistent with previous reports in the literature. , Cy-Mp can be used as a potential tool for diagnosing NAFL by tracking the polarity disorder of the liver.…”
Section: Resultssupporting
confidence: 92%
“…All the results indicate that the liver polarity of NAFL mice is lower than that of healthy mice, which was consistent with previous reports in the literature. 60,61 Cy-Mp can be used as a potential tool for diagnosing NAFL by tracking the polarity disorder of the liver.…”
Section: ■ Introductionmentioning
confidence: 99%
“…33 Meanwhile, maximum fluorescence emission successfully reached the NIR-II region at 1045 nm, and a large Stokes shift of about 185 nm was also observed. The calculated quantum yield value of CB1 was about 2.3% (reference ICG, Φ f = 13% in DMSO 34 ), which is higher than a number of reported organic NIR-II luminogens (Fig. S8 and Table S1 †), revealing the excellent potential for NIR-II imaging.…”
Section: Design Synthesis and Characterization Of Cb1mentioning
confidence: 71%
“…S11, † it was observed that the CB1 NP solution showed a conspicuous concentration-dependent fluorescence enhancement, and the quantum yield in PBS solution was found to be 0.2%. 34 The brightness (ε max Φ f ) of the CB1 NPs was 98 M −1 cm −1 , which was brighter than many other reported organic NIR-II fluorophores in aqueous solutions, such as FBP 1025 (33.3 M −1 cm −1 ) 35 and ICG-PEG 45 (3.1 M −1 cm −1 ), 36 indicating a superior potential for NIR-II bio-imaging applications. Next, the photostability of the CB1 NPs and ICG were compared.…”
Section: Papermentioning
confidence: 79%
“…Lipid droplets are highly dynamic subcellular organelles with powerful energy storage composed of various neutral lipids surrounded by a phospholipid monolayer and various complete peripheral-related regulatory proteins. Lipid droplets are involved in lipid storage and metabolism, membrane transport, and protein degradation, which have important influences on the internal environments of organisms. , Abnormalities in the activity or number of lipid droplets are closely related to metabolic diseases, such as atherosclerosis (AS), inflammation, and type II diabetes, and in diagnosing nonalcoholic fatty liver disease (NAFLD). Given the unique role of lipid droplets, real-time visual monitoring of lipid droplets in living cells and tissues is significant for revealing clinical diagnoses and biological functions.…”
mentioning
confidence: 99%